Mudanças, incertezas e significados: vivências de adolescentes com câncer no contexto hospitalar - Simionatto, Katiele (2016)
This clinical-qualitative-approach work aimed to investigate the meanings attributed by adolescents to their cancer experiences in the hospital environment. The research scenario was a Treatment Center for children with cancer, from a public hospital located in the interior of Rio Grande do Sul. The participants were adolescents between 12 and 18 years old, going through the treatment process. The participants were adolescents between 12 and 18 years old, going through the treatment process and the instrument used to collect data was semidirected interviews. The study had a total of nine participants, which was delimited based on saturation criteria, besides, the instrument of data collection was a semi-directed interview. The interviews were recorded in audio and fully transcribed, being analyzed by the technique of Content Analysis. The categories, from the analysis, were organized in two articles. The first one is about the adolescent's diagnosis of cancer, demonstrating how overwhelming the news can be for the subjects, who had never faced such a threatening disease, as well as the rupture of daily life, since it exposes the significant changes that occurs in the routine of the adolescents, evidencing the consequences of their estrangement concerning social relations. Another issue approached in the first article is the repercussions of illness, as well as the impact of the other's look on the adolescent, in other words, the stigmatization of the disease and the difficulty of having to bear the other's look considering the changes caused by the treatment (as hair loss or mask use). The first article also discusses the hospitalization of adolescents with children, in the same place. This way, the treatment center can be seen as a space that does not contemplate the psychosocial needs of hospitalized adolescents. The second article deals specifically with school dropout, finding that, due to treatment, long hospitalizations, as well as the implications of the disease and the care required, adolescents had to move away from school activities. It also explores the perception of adolescents about the hospital class - a service offered at the treatment center, which serves as a support for adolescents to continue their studies. Finally, the second article explored the difficulty of reinsertion in school environment, concerning adolescents with cancer after treatment. It is worth to highlight that the consequences of diagnosis, treatment and hospitalization, when experienced during adolescence period, may become a double problematic, since the adolescent needs to go through two complex processes: adolescence and illness. It is possible to conclude that there is a need for improvements regarding public policies and services for adolescents with cancer.